```Question 381555

Now let's FOIL the expression.

Remember, when you FOIL an expression, you follow this procedure:

{{{(highlight(x)+4)(highlight(x)+5)}}} Multiply the <font color="red">F</font>irst terms:{{{(x)*(x)=x^2}}}.

{{{(highlight(x)+4)(x+highlight(5))}}} Multiply the <font color="red">O</font>uter terms:{{{(x)*(5)=5*x}}}.

{{{(x+highlight(4))(highlight(x)+5)}}} Multiply the <font color="red">I</font>nner terms:{{{(4)*(x)=4*x}}}.

{{{(x+highlight(4))(x+highlight(5))}}} Multiply the <font color="red">L</font>ast terms:{{{(4)*(5)=20}}}.

---------------------------------------------------

So we have the terms: {{{x^2}}}, {{{5*x}}}, {{{4*x}}}, {{{20}}}

{{{x^2+5*x+4*x+20}}} Now add every term listed above to make a single expression.

{{{x^2+9*x+20}}} Now combine like terms.

So {{{(x+4)(x+5)}}} FOILs to {{{x^2+9*x+20}}}.

In other words, {{{(x+4)(x+5)=x^2+9*x+20}}}.

If you need more help, email me at <a href="mailto:jim_thompson5910@hotmail.com?Subject=Algebra%20Help">jim_thompson5910@hotmail.com</a>

Also, feel free to check out my <a href="http://www.freewebs.com/jimthompson5910/home.html">tutoring website</a>

Jim```